Resocialization, gender and the Global South: A critical analysis of the concept through women's experiences in prisons in Peru - Bracco Bruce, Lucia (Theoretical criminology, 2023)
In this article, I critically assess the concept of resocialization through discussions with women in Santa Monica Prison, the largest women's prison in Peru in 2018 and with former women prisoners in 2021. Alongside the formal, institutional gendered and classed forms and ideas of resocialization imposed by the prison, the women themselves innovate and develop new, collective and individual pathways to change. While few entirely disrupt the traditional, gendered norms and penal expectations, in their everyday experiences and collective activities, women seek, and sometimes manage to free themselves from patriarchal mandates.